Return to Intended Oncologic Therapy After Brain Metastasis Surgery: Mapping the Early Postoperative Pathway - Alexis Hadjiathanasiou; Martin Liebisch; Johanna Dahn; Johannes Lemcke; Patrick Schuss (Current Oncology, 2026)
Surgery for brain metastases (BM) is embedded in a multidisciplinary oncologic pathway. This study evaluated oncologic readiness and return to intended oncologic therapy (RIOT) after surgery for BM. Patients undergoing surgery for histologically confirmed BM were retrospectively identified. Oncologic readiness was defined as sufficient postoperative clinical and neurological recovery to allow the next indicated oncologic treatment. RIOT was defined as postoperative radiotherapy and/or systemic treatment within 30 days after surgery. Exploratory analyses assessed factors associated with oncologic readiness and RIOT after readiness. Among 126 patients, oncologic readiness was achieved in 114 (90%) and RIOT in 99 (79%). Absence of oncologic readiness was associated with postoperative morbidity and persistent neurological deficit, whereas absence of RIOT after readiness showed no distinct clinical or BM-related profile. Change in patient preference, neurological or functional deterioration, and organizational delay were the most frequent reasons for no RIOT after readiness. Oncologic readiness distinguished patients with insufficient surgical recovery from those who recovered but did not proceed to further treatment. These findings support RIOT as a process endpoint for the transition from BM surgery to postoperative oncologic care.